2006
DOI: 10.1093/condor/108.3.579
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Strategies of a Socially Monogamous Neotropical Passerine: Extra-Pair Fertilizations, Behavior, and Morphology

Abstract: Blue-black Grassquits (Volatinia jacarina) are small, granivorous, Neotropical birds that are abundant in central Brazil. During the reproductive season, the socially monogamous males acquire a blue-black plumage and defend very small, clustered territories that resemble leks. They execute a conspicuous courtship display that consists of a leap, revealing white under-wing patches, synchronized with a vocalization. We collected data on the morphology and behavior of banded males and characteristics of their ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
0
20
0
4
Order By: Relevance
“…Females then pair with territorial males, apparently ignoring most male attributes (Dias et al, ). They also appear to choose their mates disregarding male health (Aguilar et al, ), territory quality (Almeida & Macedo, ; Carvalho et al, ), and predation risk (present study). Successfully paired males in the wild have been shown to spend more time in their territories, display for longer periods and at greater rates, and produce higher leaps in their displays (Carvalho et al, ; Manica et al, ).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Females then pair with territorial males, apparently ignoring most male attributes (Dias et al, ). They also appear to choose their mates disregarding male health (Aguilar et al, ), territory quality (Almeida & Macedo, ; Carvalho et al, ), and predation risk (present study). Successfully paired males in the wild have been shown to spend more time in their territories, display for longer periods and at greater rates, and produce higher leaps in their displays (Carvalho et al, ; Manica et al, ).…”
Section: Discussionmentioning
confidence: 51%
“…At the peak of the leap, males emit a high‐pitched song and return to the perched position to leap again a few seconds later (Manica, Macedo, Graves, & Podos, ). Previous studies have shown that the height of the leap is important for male pairing success (Carvalho et al, ; Manica et al, ). Given that avian predators can capture males during their leap display (R. Macedo, pers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nuptial plumage is exhibited during the sexual display, which consists of repeated, short vertical flights from perches at the periphery of the males' small territories [40], [42], [43]. Though socially monogamous, the high rate of extra-pair fertilizations [44], associated with the lek-like clustered territories [45], [46] highlight the importance of social interactions and the strong intra- and intersexual pressures that shaped this species' mating system [47]. Females nest within male territories, and both sexes feed the offspring [43].…”
Section: Introductionmentioning
confidence: 99%